Glass-like carbon, pyrolytic graphite or nanostructured carbon for electrochemical sensing of bismuth ion? - Jadranka Milikić; Nevena Markičević; Aleksandar Jović; Radmila Hercigonja; Biljana Šljukić (Processing and Application of Ceramics, 2016)
Different carbon electrodes were explored for application in electroanalysis, namely for sensing of bismuth ion as model analyte. Carbon materials tested included glassy carbon, basal and edge plane pyrolytic graphite, as well as nanostructured carbonized polyaniline prepared in the presence of 3,5-dinitrosalicylic acid. Bismuth ion was chosen as model analyte as protocol for its detection and quantifications is still to be determined. Herein, anodic stripping voltammetry was used with study of effect of several parameters such as scan rate and deposition time. Electrode based on carbonized polyaniline showed the highest activity for bismuth ion sensing in terms of the highest current densities recorded both in a laboratory and in real sample, while basal plane pyrolytic graphite electrode gave the lowest limit of detection.